Best additional management after non-curative endoscopic resection of esophageal squamous cell carcinoma: a systematic review and meta-analysis. (4th May 2022) - Flor de Lima, Margarida; Castro, Bárbara; Rodríguez-Carrasco, Marta; Libânio, Diogo; Pimentel-Nunes, Pedro; Sousa, Olga; Dinis-Ribeiro, Mário
Abstract: Introduction: Endoscopic resection (ER) is an accepted first-line treatment for superficial esophageal squamous cell carcinoma (ESCC), but when curative resection is not achieved, further treatment is not standardised. We aimed at evaluating outcomes of management strategies (esophagectomy, chemoradiotherapy/radiotherapy (CRT/RT) or follow-up (FUP)) after a non-curative ESCC ER. Methods: A systematic review was performed evaluating outcomes of different management strategies after ESCC submitted to primary ER (T1a/T1b), without curative criteria (R1/Rx, T1a-m3/T1b, lymphovascular invasion (LVI) or poor differentiation). Primary outcomes included recurrence, overall survival (OS) and cancer-specific survival (CSS). Secondary outcomes consisted of treatment-related adverse events. Results: Seventeen studies were included for qualitative analysis (16 observational and 1 randomized controlled trial) including 788 patients with ESCC submitted to ER, managed by additional CRT/RT ( n = 530), surgery ( n = 98) or FUP ( n = 160). Eight studies suited quantitative analysis. Patients only followed up after ER experienced recurrence rates of 0–36.4% (OR 3.6 (95%CI 1.06–12.20) vs further treatments). When submitted to CRT/RT following non-curative ER, recurrence was observed in 0–27.2% (OR 8.00 (95%CI 1.74–36.80) whereas after surgery no recurrence was noticeable. Reported 5 y-OS after CRT/RT for non-curative ER ranged among 75–100% whereas, for those offered surgeries, 5 y-OS was 89.5%. OS ranged between 54.5% and 100% after FUP. CRT/RT and surgery-related adverse events ranged from 0% to 32% and 14% to 28.5%. Conclusions: Additional treatment should be provided in ESCC after non-curative ER. Adjuvant esophagectomy might be the preferred treatment to medically fit patients with high-risk features (namely LVI). Properly designed trials assessing the role of CRT/RT are needed to manage these patients.